Anatomic variation of celiac axis and hepatic artery as evidenced in multidetector computed tomography in patients at tertiary care center in Nepal - Maharjan, Dinesh; Sherpa, Ngawang; Kharel, Amrit; Gyawali, Sushila (Journal of Patan Academy of Health Sciences, 2022)
Introduction: There are many potential anatomic configurations of celiac axis and hepatic artery. Michel’s classified hepatic arterial variations in 10 categories. Knowledge about these variations in patient is invaluable before surgery. Multidetector computed tomography (MDCT) can accurately depict the vascular anatomy of celiac axis and hepatic artery non-invasively. The aim of this study was to find out the prevalence of different types of anatomical variation of celiac axis and hepatic artery in patients undergoing multiphase CT.Method: Cross-sectional, prospective study was done in Department of Radiology, Patan Hospital, Patan Academy of Health Sciences. MDCT of abdomen of 178 patients with arterial phase images done between December 2021 and March 2022 were evaluated for arterial anatomy of celiac axis and hepatic artery. Arterial anatomy was categorized according to Michel’s classification. Prevalence of each variant anatomy and gender wise prevalence were calculated.Results: CT scans of 178 patients were evaluated out of which 94 were male and 84 were female. Among these individuals 133 (74.7%) had normal anatomy (Type I) and 45 (25.3%) had some sort of variant anatomy. Type III was commonest type of variant anatomy seen in 18 (10.1%) individuals. We found 6(3.4%) individuals with the anatomy other than classified by Michel.Conclusion: There are multiple variation in of celiac axis and hepatic artery anatomy in our population. Knowledge of such anatomical variation will be of great importance for surgeon and interventional radiologist for planning of surgical or vascular procedures and to prevent vascular complication.